SOLIDARITAS MASYARAKAT PINGGIRAN - Aswadi, Aswadi; Murtafik Haris, Ahmad (Prodi Sosiologi, Fakultas Ilmu Sosial dan Ilmu Politik, UIN Sunan Ampel Surabaya, 2012)
Society is divided into classifications. Some groups live in the city center and some others in its peripheries. The former gains privileges which ascribes to his better economic condition and the latter is inversely living in poverty and limit of access to individual development. Peripheries society is often harmful by a system which gives no attention to lift their hindrances. Some reason which keeps them in poverty is due to the lack or crisis of solidarity which is very fundamental in society building. All groups are supposed to be interconnected each other within social network in order to live in harmony. The unlifted sufferings among poor people indicates the broken social network between groups and layers which needs resolving and reshaping collective consciousness among members of society. Kata Kunci : solidaritas, masyarakat pinggiran